2014
DOI: 10.1155/2014/813201
|View full text |Cite
|
Sign up to set email alerts
|

Canthium parviflorumLeaves: Antioxidant Activity in Food and Biological Systems, pH, and Temperature Stability

Abstract: Canthium parviflorum leaves were analyzed for their proximate and phytochemical composition. The leaves were extracted with methanol (ME) and analyzed for antioxidant activity by radical scavenging method, reducing power, ferric reducing capacity, and in vitro inhibition of Fenton's reagent induced oxidation in oil emulsion and microsomes. In addition, the effect of high temperature (100 ∘ C, 15 and 30 min) and pH (4.5, 7, and 9) on the antioxidant activity of ME was investigated. The leaves were rich in polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies also report that they exhibit good antioxidant activity in vitro [13, 31] Table 1 depicts the phytochemical composition of the samples, where it was observed that CS and AnP were good sources of polyphenols, glutathione, β -carotene, total saponins, and steroidal saponins, whereas AP and CP were found to be good sources of flavonoids, alkaloids, α -tocopherol, vitamin C, and tannins.…”
Section: Resultsmentioning
confidence: 99%
“…Studies also report that they exhibit good antioxidant activity in vitro [13, 31] Table 1 depicts the phytochemical composition of the samples, where it was observed that CS and AnP were good sources of polyphenols, glutathione, β -carotene, total saponins, and steroidal saponins, whereas AP and CP were found to be good sources of flavonoids, alkaloids, α -tocopherol, vitamin C, and tannins.…”
Section: Resultsmentioning
confidence: 99%